Cavum septi pellucidi (CSP) ratio: a marker for partial agenesis of the fetal corpus callosum. (9th August 2017) - Karl, K.; Esser, T.; Heling, K. S.; Chaoui, R.
ABSTRACT: Objective: While complete agenesis of the corpus callosum is often suspected on fetal ultrasound due to absence of the cavum septi pellucidi (CSP), suspicion of partial agenesis of the corpus callosum (pACC) is a challenge since the CSP is almost always present. The aim of this study was to measure the length and width of the CSP and calculate the length‐to‐width ratio (CSP ratio), and compare these between fetuses with pACC and normal fetuses. Methods: In this retrospective case–control study, the length and width of the CSP were measured in the axial plane of the fetal head, and the CSP length‐to‐width ratio calculated, in 323 normal fetuses and in 20 fetuses with pACC between 20 and 34 weeks' gestation. From the normal population we constructed reference ranges in relation to biparietal diameter (BPD). For all fetuses we calculated Z ‐scores for the CSP ratio. Results: In the normal population, the length and width of the CSP increased with increasing BPD, while the CSP ratio decreased. The CSP was short (< 5 th centile) in 85% (17/20) of fetuses with pACC and wide (> 95 th centile) in 65% (13/20). The CSP ratio was small (< 5 th centile) in 95% (19/20) of pACC fetuses, with 16/20 (80%) having a ratio below an empirical cut‐off of 1.5. Analysis of Z‐scores showed that fetuses with pACC had a significantly smaller CSP ratio ( P < 0.0001) compared with the normal population. Conclusions: Fetuses with a normal‐sized corpus callosum have a rectangular‐shaped CSP, with a CSP ratio > 1.5 in the second half of gestation. Most fetuses with pACC have an abnormally shaped, wide and short CSP, with a decreased CSP ratio. This simple ratio has the potential to identify fetuses at high risk for pACC. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.